Public sector ethics : finding and implementing values - Sampford, C. J. G. (Charles J. G.); Preston, Noel, 1941-; Bois, C.-A. (Carol-Anne), 1960- (Routledge studies in governance and public policy ;, 1998)
This study, with contributions from both scholars and practitioners, examines the theory and practice of public sector ethics across a broad range of environments.